Karakteristik Fisik dan Sensoris Daging Tiruan Berbasis Kedelai dan Glukomanan untuk Intervensi Gizi Obesitas: Karakteristik Fisik dan Sensoris Daging Tiruan Berbasis Kedelai dan Glukomanan untuk Intervensi Obesitas - Purnawijayanti, Hiasinta Anatasia; Pujiastuti, Veronica Ima; Wijayanti, M.I. Ekatrina (Universitas Airlangga, 2024)
Background: Foods low in calories, low in fat, high in protein and fiber can be an option for treating obesity. Soy protein is high quality and low fat, while glucomannan is a fiber with low energy density. In this research, artificial meat based on soybeans and glucomannan was developed with low calories and fat but high protein and fiber for obesity intervention. Objectives: This research aims to develop soybean and glucomannan-based meat analogue for obesity interventions and determine the physical and sensory characteristics of soy and glucomannan-based meat analogue. Methods: This study was an experimental study with a completely randomized design, four treatment proportions (%) of soybean protein isolate-glucomannan (30:0, 29:1, 27:3, and 25:5) and three treatment replications. The data collected included physical test data (water holding capacity and cooking loss), and sensory test data (appearance, texture, aftertaste, and preferences). According to the data category, physical test data were analyzed using Variance Analysis or Kruskal Wallis. Sensory test data were analyzed using analysis of variance followed by the post hoc Duncan Multiple Range Test. Results: The proportion of soy protein isolate-glucomannan did not affect the water binding capacity and cooking loss. The water binding capacity ranges from 12.44 to 34.61%, and the cooking loss ranges from 2.17 to 4.44%. The sensory score for the appearance, taste, and texture was neither resembling (score 2) nor somewhat resembling (score 3) chicken meat. The proportion of soy protein isolate-glucomannan influences the appearance and texture but does not influence the taste, aftertaste, and level of liking. The aftertaste scores are strong and moderate. The liking score was between dislike and somewhat like. Conclusions: Meat analogue for obesity intervention can be developed using soybeans and glucomannan. The cooking loss and water-holding capacity of artificial meat are proper, while the sensory characteristics of meat analogue do not yet resemble real meat.